Aplikasi E-Catering Berbasis Website Menggunakan Metode Waterfall (Studi Kasus: Joca Catering) - Priskila, Ressa; Senas, Jonathan Markus (Journal of Information Technology and Computer Science, 2021)
Joca Catering is one of the home catering services in the city of Palangka Raya and has been established since 2015. This caterer has served various catering needs, ranging from households to offices. Joca Catering also offers food, cakes, and drinks. Generally, Joca Catering customers know about this catering service by word of mouth, because so far Joca Catering has promoted their business using the WOM (word of mouth) marketing method. This method is still considered inadequate for reaching a wider market, especially among young people. So Joca felt the need to replace their old marketing concept with the concept of online food ordering (e-catering). This research aims to build a website-based e-catering application that is able to become Joca Catering's marketing and sales medium. The development methodology used in making this website application is the waterfall development method. The result of this study is a website-based e-catering application that can provide information for visitors and customers about the food menu provided and can be used to order food menus.